METHODS OF OBTAINING HEAT AND ELECTRICITY FROM SOLAR ENERGY - Qurbonova, Barno; Qurbonov, Abror (Физико-технологического образование, 2024)
Today, renewable energy sources are widely used to meet the demand for thermal energy. This article presents an analysis of today’s perspective projects of solar heat supply systems